The Amended European Environmental Impact Assessment Directive: UK marine experience and recommendations. (1st November 2017) - Lonsdale, Jemma; Weston, Keith; Blake, Sylvia; Edwards, Ruth; Elliott, Michael
Abstract: Environmental Impact Assessments (EIAs) are a key legislative requirement used to ensure sustainable development. A notable example of the enabling legislation is the European Union Environmental Impact Assessment Directive (2011/92/EU). In the 25 years since its implementation it has been revised, most recently in 2014, with amendments to accommodate policy, legal and technical changes. The 2014 amendment to the EIA Directive is reviewed here in the marine context with areas identified where the Directive and its implementation may still be deficient. This arises from the experience of the authors of reviewing EIAs, and our recommendations are mainly that standardised guidance and approaches should be applied for comparability. These recommendations have general relevance to all EIA practitioners, not just marine, and to environmental assessments within and beyond the EU. Highlights: Shortcomings of the EIA Directive and process are identified and discussed. Recommendations are made for consistent and robust implementation of the Directive. Recommendations are made to address outstanding limitations of the EIA Directive. These recommendations are relevant to terrestrial and marine EIA practitioners.